Ingredients for growth: Examining electricity consumption and complementary infrastructure for Small and Medium Enterprises in Kenya. (2021) - Muhwezi, Bob; Williams, Nathaniel J.; Taneja, Jay
Abstract: In Kenya, between 2010 and 2015, the number of Small and Medium Enterprises (SMEs) connected to the grid increased by over 60%. Despite this substantial increase, little is known about the behavioural patterns or conditions that contribute to increased electricity consumption among these SMEs. This study addresses the problem through a longitudinal analysis of monthly electricity bills for over 179, 000 grid connected SMEs in Kenya. We then leverage multiple publicly available geospatial datasets to estimate how complementary infrastructural variables (such as access to roads, markets, financial services, and macro/micro-economic conditions) correlate with sustained electricity consumption growth by SMEs. Results from our longitudinal analysis indicate that newly electrified SMEs in urban areas have higher median consumption than their older counterparts while in rural areas, more newly connected SMEs appear to have lower median consumption. We find the effects of complementary infrastructure on SME electricity consumption to be more pronounced in rural areas than urban areas. For example, SMEs located in rural neighbourhoods with close proximity to roads, markets or financial service providers are associated with a 10% to 16% increase in electricity consumption while in urban areas, we only observe about a 2% increment in electricity consumption for SMEs within close proximity to roads. All other infrastructural variables are either statistically insignificant or negatively correlated with urban SME electricity consumption.